Cholesteryl Ester Transfer Protein, Coronary Calcium and Intima-media Thickness of the Carotid Artery in Middle-Aged Japanese Men - Okamura, Tomonori (2009)
The relationship between cholesteryl ester transfer protein (CETP) levels and atherosclerosis is controversial. We examined whether serum CETP levels were associated with subclinical atherosclerosis independent of its most common gene variant in a sample of Japanese men. A population-based cross-sectional study in 250 Japanese men aged 40–49 was conducted to assess intima-media thickness of the carotid artery (IMT), coronary artery calcium (CAC), serum CETP levels, and the CETP D442G gene variant. Compared with the lowest CETP quartile, multivariate adjusted odds ratios for CAC were 0.77 (95 % confidence interval [CI], 0.18 to 3.36), 0.96 (95% CI, 0.27 to 3.40), and 3.49 (95% CI, 1.05 to 11.6) with rising CETP quartiles. Serum CETP quartiles were also positively associated with IMT (adjusted means were 600, 616, 617 and 646 [μm] in the bottom to top quartiles). Findings remained unchanged after further adjustment for the CETP D442G gene variant. There was no significant difference in the prevalence of CAC, or in the mean IMT, between participants with and without the CETP D442G gene variant.